The Impact of the Termination of Administrative Decisions on Acquired Rights - سعيد, زانا جلال (Sulaimani Journal for Humanities, 2020)
This study, consider the extent of the administration’s authority to end administrative decisions in the way of canceling and revoking either individual or organizational administrative decisions. This study also endeavors to distinguish between revocation and cancelation in terms of their effects on decisions in relation to the past and the future decisions. In addition, this study discussed the concept and sources of the acquired rights, since administrative decisions are among the legal actions of the administration that generate legal centers for individuals addressed to the decision; and therefore they acquire individual’s rights in their own right. In effect, this paper examined both legitimate and illegal administrative decisions the two most important sources of these rights. Given the broad powers that the administration enjoys towards individuals, it can cancel or revoke its decisions according to developments in the functioning of public facilities management or rendering to the requirements of the public interest. Furthermore, and since individuals in their relations with the administration are considered the weaker party, the law provides for their protection, so they are preserved the legal rights and positions which they acquired from the law or from the decisions issued by the administration concerning them. Consequently, the administration is prevented from violating these acquired rights and positions, and that is in implementation of the necessary stability of the rights and legal positions.